Analysis of Singapore real estate investment trusts (S-REITs). - Liew, Jiun Bin. (2009)
In this paper, we explore the performance of Singapore Real Estate Investment Trusts (S-REITs) relative to bonds and equities asset classes. The Sharpe Ratio was used as an indicator of risk-return efficiency to determine if S-REITs could be included into a typical portfolio of bonds and equities to provide diversification benefits. Results of our investigations revealed that the S-REITs indeed provided diversification benefits despite a slight deviation from the performance of REITs in other geographical regions. Of the factors that affected the risk-return efficiency of S-REITs, it was found that two main factors, namely, credit worthiness and earnings stability, had the most significant impact on S-REITs in maximizing their risk-return efficiency. However, investors should be aware that S-REITs have yet to undergo a full business cycle and the local market has yet to acquire a holistic view of the performance of S-REITs.